The Role of Organizational Commitment as a Mediation Variable in the Influence of Emotional Intelligence and Work Discipline on Employee Performance in The Police and Firefighting Units of Klungkung Regency - GAYATRI, Sukma; SUGIATI, Gusti Ayu; SURASMI, Ida Ayu (International Journal of Environmental, Sustainability, and Social Science, 2025)
Regional governments are responsible for public services through agencies like the Public Order Agency (Satpol PP). In Klungkung Regency, Satpol PP’s performance from 2021–2024 averaged 96.15%, falling short of targets. SKP data and absence rates also highlight performance issues. Field observations suggest low emotional intelligence, poor work discipline, and weak organizational commitment as key factors, reflected in employees’ inability to manage emotions, lack of punctuality, and limited loyalty to the organization. This study aims to determine the effect of emotional intelligence and work discipline on employee performance, with organizational commitment as a mediating variable, at the Klungkung Regency Satpol PP. The population in this study was all 73 civil servants of the Klungkung Regency Satpol PP. This study used a census to select all employees, with an initial sample size of 73. However, unit heads were excluded from the sample, resulting in a total of 72 respondents. The data collection method was a questionnaire. The analytical technique used to answer the hypotheses was inferential analysis using Partial Least Squares (PLS). The study found that emotional intelligence positively influenced organizational commitment but did not directly affect performance. Work discipline negatively affected performance but positively influenced commitment. Organizational commitment had a significant positive impact on performance, fully mediating the effect of emotional intelligence and partially mediating the effect of work discipline. To enhance performance, leaders should provide emotional training, improve communication, and enforce discipline, while employees should strengthen emotional control, discipline, and commitment.